Analisis Pengelolaan Dana Desa Ditinjau Dari Perspektif Manajemen Keuangan Syariah di Desa Pagar Puding Lamo Kabupaten Tebo - Sariani Sariani; Bambang Kurniawan; Eri Nofriza (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the management of village funds in Pagar Puding Lamo Village, Tebo Regency from the perspective of sharia financial management. This research is a type of qualitative research using descriptive analysis. Descriptive analysis is data obtained and expressed in the form of words and images, so that it can be described to provide clarity. This research uses data collection methods by means of observation, interviews and documentation. The results of this research indicate that the management of village funds in Pagar Puding Lamo Village is in accordance with Permendagri No. 113 of 2014 starting from the planning, implementation, administration, reporting and accountability stages. In the review of sharia management regarding the management of village funds, it is clear that the management still does not implement the sharia system, the system used still tends to be conventional, but judging from the nature and values ​​of honesty, trust and fair sharia in its management, village officials have implemented it in managing village finances.